The inflammasome in biomaterial‐driven immunomodulation. (3rd November 2022) - Vasconcelos, Daniela P.; Águas, Artur P.; Barbosa, Judite N.
Abstract: Inflammasomes are intracellular structures formed upon the assembly of several proteins that have a considerable size and are very important in innate immune responses being key players in host defense. They are assembled after the perception of pathogens or danger signals. The activation of the inflammasome pathway induces the production of high levels of the pro‐inflammatory cytokines Interleukin (IL)‐1β and IL‐18 through the caspase activation. The procedure for the implantation of a biomaterial causes tissue injury, and the injured cells will secrete danger signals recognized by the inflammasome. There is growing evidence that the inflammasome participates in a number of inflammatory processes, including pathogen clearance, chronic inflammation and tissue repair. Therefore, the control of the inflammasome activity is a promising target in the development of capable approaches to be applied in regenerative medicine. In this review, we revisit current knowledge of the inflammasome in the inflammatory response to biomaterials and point to the yet underexplored potential of the inflammasome in the context of immunomodulation.